Movement accuracy theory: most problematic aspects - Lukyanenko, V. P. (Theory and Practice of Physical Culture, 2018)
Despite the long history or research of the movement accuracy related issues and the ample research materials accumulated in the modern science, the key theoretical basics of the movement accuracy knowledge appear to be still underdeveloped. One of the possible reasons for that is that the relevant studies still give a high priority to the extensive research methods that produce mostly quantitative rather than qualitative study data. Most popular in the research practices at this juncture is a variety of inefficient and often inappropriate test methods that are designed to rate elementary movements in limited environments that have nothing similar to the real physical training and sporting motor skills. No wonder that such study data, data analyses and interpretations often result in totally valueless or deeply erroneous findings. The study makes an attempt to outline the present situation with the movement accuracy theory making a special emphasis on the most controversial theoretical and practical aspects that need to be addressed to improve the quality of the movement accuracy tests and analyses; and outlines the potentially most promising avenues for research in the field.